Hole transport layer, preparation method and solar cell

By using the first and second transition group metal oxides arranged stacked as hole transport layers in the solar cell, the efficiency limitation problem caused by the contact between the metal electrode and silicon is solved, and efficient hole selectivity and transmission performance are achieved. The photoelectric conversion efficiency of solar cells is improved and the preparation process is simplified.

CN119173050APending Publication Date: 2024-12-20ZHEJIANG SCI-TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411284365.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-05-10
Filing Date
2024-09-13
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

In existing solar cells, the direct contact between metal electrodes and silicon leads to the Fermi level pinning effect and Auger recombination, limiting the battery efficiency, and the high work function transition group metal oxides are difficult to maintain the metering ratio under preparation and environmental conditions, resulting in The competition of hole transport mechanisms makes it impossible to achieve efficient hole selectivity and transmission at the same time.

Method used

The first transition group metal oxide and the second transition group metal oxide arranged in a stack are used as the hole transport layer. The second transition group metal oxide is closer to the stoichiometric ratio than the first transition group metal oxide, and the first transition is used. The oxygen vacancy in the group metal oxide causes a trap-state assisted tunneling mechanism, and the high work function of the second transition group metal oxide induces the bending of the surface energy band, achieving improved hole selectivity and transmission performance.

Benefits of technology

Through the synergistic trap-state assisted tunneling and inter-band tunneling mechanism, efficient hole selectivity and transmission performance are achieved, the photoelectric conversion efficiency of solar cells is improved, and the preparation process is simplified and the cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119173050A_ABST
    Figure CN119173050A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of batteries, and particularly relates to a hole transport layer, a preparation method and a solar cell, and the hole transport layer comprises a first transition metal oxide and a second transition metal oxide which are stacked. The second transition group metal oxide is closer to the stoichiometric ratio than the first transition group metal oxide. The first transition group metal oxide promotes holes to be transmitted in a trap state auxiliary tunneling mechanism, the second transition group metal oxide promotes the holes to be transmitted in an inter-band tunneling mechanism, and the two hole transmission mechanisms have a synergistic effect. The high-work-function transition metal oxide laminated layer is used as a hole transport layer of the solar cell, so that high carrier selective transport is realized, and the efficiency of the solar cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and in particular relates to a hole transport layer, a preparation method and a solar cell. Background Art

[0002] At present, mankind is facing the contradiction between the shortage of fossil energy and the huge energy demand, as well as a series of environmental problems caused by fossil fuels, such as air pollution and climate change. As a renewable energy, solar photovoltaic power generation has the advantages of being inexhaustible and will be one of the widely used energy sources in the future.

[0003] In the photovoltaic market share, crystalline silicon solar cells account for more than 95%. Commercial silicon solar cells mainly adopt the passivated emitter and rear cell (PERC) structure. Compared with the theoretical conversion efficiency of silicon solar cells of 29.4%, industrial cells still have a lot of room for improvement. The main limiting factor of PERC cell efficiency comes from the direct contact between metal electrodes and silicon. The metal introduces defect states in the silicon bandgap, resulting in the Fermi level pinning effect, and the Auger recombination produced by the heavily doped silicon layers on the front and back surfaces. Carrier selective contact has attracted widespread attention, represented by HIT and TOPCon solar cells, which introduce intrinsic / doped a-Si:H or ultra-thin SiO between silicon and metal. x However, their process equipment is complex, costly, and the gas sources of intrinsic and doped a-Si:H are dangerous.

[0004] Transition metal oxides (TMOs) have excellent carrier selection properties and have advantages such as wide bandgap, adjustable work function, and low-temperature preparation process. As carrier selection layers, they form non-doped heterojunction solar cells with silicon, which has attracted much attention. TMOs with high work functions can induce the upward bending of the silicon surface energy band, achieving hole-selective contact. As hole transport layer (HTL) materials, TMOs with high work functions have simple preparation processes, such as low-temperature deposition or solution-based methods, and offer great potential in terms of low cost and process simplification. Seo's research group used MoO x Applied to the back-mounted battery structure, without superimposed interface passivation layer, the battery efficiency reached 12.8% (UmHD, KimN, LeeK, et al. Nano letters, 2016, 16(2): 981-987.). Ali Javey's research group at the University of California, Berkeley, thermally evaporated MoO xApplied to crystalline silicon solar cells, combined with back passivation, Voc is 580mV and the efficiency reaches 14.3% (BattagliaC, DeNicolas SM, DeWolf S, et al. Applied Physics Letters, 2014, 104(11): 113902.). There are two hole transport mechanisms in high work function TMO / Si heterojunction: band-to-band tunneling (B2B) transport mechanism and trap-assisted tunneling (TAT) transport mechanism. Among them, B2B transport requires TMO to have a high work function, that is, a high stoichiometric ratio, inducing a large band bending on the silicon surface and achieving high hole selectivity; TAT transport requires TMO to have more oxygen vacancies, and oxygen vacancy-related trap states assist hole transport. High work function TMO thermodynamically tends to lose oxygen, and is affected by factors such as preparation conditions, external environment (air, heating) and contact with silicon devices, making it difficult to obtain a stoichiometric TMO. In the commonly prepared high-work-function TMO / Si heterojunction, two hole transport mechanisms coexist, which compete or contradict each other and cannot be realized simultaneously. Summary of the invention

[0005] The present invention provides a hole transport layer, a preparation method and a solar cell. The hole transport layer can effectively adjust the selectivity and transport of holes and improve the photoelectric conversion efficiency of the solar cell.

[0006] In order to solve the above technical problems, the present invention provides a hole transport layer, comprising a first transition metal oxide and a second transition metal oxide stacked in layers, wherein the second transition metal oxide is closer to a stoichiometric ratio than the first transition metal oxide.

[0007] That is, relative to the first transition group metal oxide, the second transition group metal oxide is closer to the stoichiometric ratio and has a smaller amount of oxygen vacancies; whereas the stoichiometric ratio of the first transition group metal oxide is not close to the stoichiometric ratio and has a larger amount of oxygen vacancies.

[0008] In some embodiments, the first transition group metal oxide comprises MoO 3-x , WO 3-y 、V 2 O 5-z One or more of the following, wherein x<2.8, y<2.8, z<4.7. The second transition metal oxide includes MoO 3-x , WO 3-y 、V 2 O 5-z One or more of the following, where x≥2.8, y≥2.8, z≥4.7.

[0009] In some embodiments, the first transition group metal oxide is doped with a low-valent metal cation having a chemical valence state lower than the chemical valence state of the transition group metal cation in the first transition group metal oxide.

[0010] In some embodiments, the low-valent metal cation comprises V 5+ ,Nb 5+ ,Ta 5+ ,Sn 4+ , Al 3+ , Ni 2+ One or more of the .

[0011] In some embodiments, the work function of the first transition group metal oxide is greater than or equal to 4.7 eV, and the work function of the second transition group metal oxide is greater than or equal to 5.5 eV.

[0012] In some embodiments, the thickness of the first transition group metal oxide and the second transition group metal oxide are both 1-15 nm.

[0013] The present invention also includes a second technical solution, a method for preparing a hole transport layer, comprising:

[0014] forming a first transition group metal oxide on a substrate;

[0015] A second transition group metal oxide is formed on a side of the first transition group metal oxide facing away from the substrate, and the second transition group metal oxide is closer to a stoichiometric ratio than the first transition group metal oxide.

[0016] In some embodiments, preparing a first transition metal oxide on a substrate includes: spin coating a first precursor solution mixed with low-valent metal cations on the substrate, and heating the solution to obtain the first transition metal oxide.

[0017] In some embodiments, the ratio of the amount of the low-valent metal cation to the amount of the first precursor in the first precursor solution is (1-10):100.

[0018] In some embodiments, preparing a first transition metal oxide on a substrate includes: spin coating a first precursor solution on the substrate, heating it, and then annealing it in a reducing atmosphere, an inert atmosphere or vacuum conditions to obtain the first transition metal oxide.

[0019] In some embodiments, the annealing temperature is 100-200° C., and the annealing time is 5-20 minutes.

[0020] In some embodiments, preparing the second transition metal oxide on the side of the first transition metal oxide facing away from the substrate includes: vacuum evaporating a second precursor oxide on the side of the first transition metal oxide facing away from the substrate to obtain the second transition metal oxide.

[0021] The present invention also includes a third technical solution, a solar cell, comprising the hole transport layer described above, or the hole transport layer prepared by the above preparation method.

[0022] In some embodiments, from top to bottom, the structure also includes a silver electrode gate line, a silicon nitride passivation layer, an N-type emitter, a P-type single crystal silicon substrate and a silver electrode. The hole transport layer is located between the P-type single crystal silicon substrate and the silver electrode. The first transition metal oxide of the hole transport layer is close to the P-type single crystal silicon substrate side, and the second transition metal oxide of the hole transport layer is located on the side of the first transition metal oxide away from the P-type single crystal silicon substrate.

[0023] Beneficial effects:

[0024] (1) The hole transport layer of the present invention includes a first transition metal oxide and a second transition metal oxide which are stacked. The first transition metal oxide promotes hole transport by a trap state assisted tunneling mechanism, and the second transition metal oxide promotes hole transport by an inter-band tunneling mechanism. The trap state assisted hole transport caused by more oxygen vacancies in the first transition metal oxide is utilized, and the higher work function of the second transition metal oxide induces a greater bending of the silicon surface energy band, thereby enhancing the selectivity of holes. The two mechanisms act synergistically, and at the same time, the mechanism of hole trap state assisted tunneling and the mechanism of inter-band tunneling can be separately regulated to achieve better results and realize high hole selectivity and transport performance. The first transition metal oxide and the second transition metal oxide are stacked as the hole transport layer of the solar cell to achieve high selective transport of carriers and improve the efficiency of the solar cell.

[0025] (2) The preparation method of the hole transport layer of the present invention is simple in process and high in efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is a schematic structural diagram of a solar cell according to an embodiment of the present invention;

[0027] Figure 2 1 is a JV curve diagram of the solar cells of Example 1 of the present invention and Comparative Example 1;

[0028] Figure 3 2 is a JV curve diagram of the solar cells of Example 2 of the present invention and Comparative Example 2;

[0029] Figure 43 is a JV curve diagram of the solar cells of Example 3 of the present invention and Comparative Example 3;

[0030] Figure 5 τ of p-Si with hole transport layer passivation in Example 2 of the present invention and Comparative Example 2 eff picture;

[0031] Figure 6 Energy band diagram of the hole transport layer in contact with p-Si in Example 2 of the present invention and Comparative Example 2. DETAILED DESCRIPTION

[0032] An embodiment of the present application provides a hole transport layer, comprising a first transition group metal oxide and a second transition group metal oxide stacked in layers, wherein the second transition group metal oxide is closer to a chemical dosage ratio than the first transition group metal oxide.

[0033] In the embodiment of the present application, the second transition metal oxide is closer to the chemical dosage ratio than the first transition metal oxide, and the work function of the second transition metal oxide is greater than or equal to the work function of the first transition metal oxide. The trap state caused by the large number of oxygen vacancies in the first transition metal oxide is used to assist hole transport, and the higher work function of the second transition metal oxide induces a larger bending of the silicon surface energy band, thereby enhancing the selectivity of holes. The two mechanisms work synergistically, and at the same time, the mechanism of separately regulating holes to assist tunneling with trap states and the mechanism of inter-band tunneling can also be achieved, so as to achieve better results and realize high hole selectivity and transport performance.

[0034] In some embodiments, the first transition group metal oxide comprises MoO 3-x , WO 3-y 、V 2 O 5-z One or more of the following, wherein x<2.8, y<2.8, z<4.7. The second transition metal oxide includes MoO 3-x , WO 3-y 、V 2 O 5-z One or more of the following, where x≥2.8, y≥2.8, z≥4.7.

[0035] In some embodiments, the first transition metal oxide is doped with a low-valent metal cation, and the chemical valence of the low-valent metal cation is lower than the chemical valence of the transition metal cation in the first transition metal oxide. The low-valent metal cation has an ionic radius similar to that of the transition metal cation in the first transition metal oxide, which is advantageous for being in a substitution position and increasing oxygen vacancies.

[0036] In some embodiments, the low-valent metal cation comprises V 5+ ,Nb 5+,Ta 5+ ,Sn 4+ , Al 3+ , Ni 2+ One or more of the .

[0037] In some embodiments, the work function of the first transition metal oxide is greater than or equal to 4.7 eV, and the work function of the second transition metal oxide is greater than or equal to 5.5 eV. In the embodiment of the present application, the second transition metal oxide is a high work function transition metal oxide.

[0038] In some embodiments, the thickness of the first transition group metal oxide and the second transition group metal oxide are both 1-15 nm.

[0039] The present invention also includes a second technical solution, a method for preparing a hole transport layer, comprising:

[0040] forming a first transition group metal oxide on a substrate;

[0041] A second transition group metal oxide is formed on a side of the first transition group metal oxide facing away from the substrate, and the second transition group metal oxide is closer to a chemical dosage ratio than the first transition group metal oxide.

[0042] In some embodiments, preparing a first transition metal oxide on a substrate includes: spin coating a first precursor solution mixed with low-valent metal cations on the substrate, and heating the solution to obtain the first transition metal oxide.

[0043] In some embodiments, the ratio of the amount of the low-valent metal cation to the amount of the first precursor in the first precursor solution is (1-10):100.

[0044] In some embodiments, the first transition metal oxide is prepared on a substrate, comprising: spin coating a first precursor solution on the substrate, heating the substrate, and then annealing the substrate in a reducing atmosphere, an inert atmosphere, or a vacuum condition to obtain the first transition metal oxide. The reducing atmosphere is generally a H-containing 2 of mixed gas.

[0045] In some embodiments, the annealing temperature is 100-200° C., and the annealing time is 5-20 minutes.

[0046] In some embodiments, preparing the second transition metal oxide on the side of the first transition metal oxide facing away from the substrate comprises: vacuum evaporating a second precursor oxide on the side of the first transition metal oxide facing away from the substrate to obtain the second transition metal oxide. The oxygen vacancies of the second transition metal oxide can be regulated by adjusting the vacuum degree and oxygen content.

[0047] The present invention also includes a third technical solution, a solar cell, comprising the hole transport layer described above, or the hole transport layer prepared by the above preparation method.

[0048] In some embodiments, from top to bottom, the structure also includes a silver electrode gate line, a silicon nitride passivation layer, an N-type emitter, a P-type single crystal silicon substrate and a silver electrode. The hole transport layer is located between the P-type single crystal silicon substrate and the silver electrode. The first transition metal oxide of the hole transport layer is close to the P-type single crystal silicon substrate side, and the second transition metal oxide of the hole transport layer is located on the side of the first transition metal oxide away from the P-type single crystal silicon substrate.

[0049] For ease of understanding, the following specific implementation is provided. It should be noted that the silicon wafers used in the following examples and comparative examples are p-type silicon wafers with a resistivity of 0.8 to 2 Ω·cm. <100> Example 1: Silicon wafer with a thickness of 170 μm

[0050] The preparation of solar cells includes the following steps:

[0051] 1) The surface of the silicon wafer is treated with a 1% NaOH aqueous solution to form an inverted pyramid-shaped velvet structure. The treated silicon wafer is then immersed in a hydrofluoric acid aqueous solution to remove the surface oxide layer and residual NaOH, and then repeatedly rinsed with deionized water to obtain a treated P-type single crystal silicon substrate (p-Si).

[0052] 2) On the first surface of p-Si, POCl 3 As a diffusion source, the P element is diffused to the front surface of p-Si through high temperature treatment to form n + Subsequently, laser doping is performed at specific locations on the silver gate to obtain an N-type emitter.

[0053] 3) Immerse the p-Si back surface (second surface, ie, away from the first surface) after the above treatment in a diluted HF solution to remove the phosphosilicate glass on the back surface and the edge of the silicon wafer to obtain a treated silicon wafer.

[0054] 4) immersing the silicon wafer treated in step 3) in a 1.5% NaOH aqueous solution, and performing a secondary polishing treatment on the edge of the back surface of the silicon wafer;

[0055] 5) On the first surface of the silicon wafer treated in step 4), a 70 nm thick SiNx:H film was deposited by PECVD process as a passivation layer and an anti-reflection layer to obtain a pretreated silicon wafer. Subsequently, a silver grid was prepared by screen printing and heated at 850 °C. O Silver electrode was obtained by rapid sintering at C temperature.

[0056] 6) Add 50 μL of triisopropyl vanadium oxide to 10 mL of anhydrous ethanol and sonicate for 20 min to obtain V 2 O 5-X Precursor solution. Place the silicon wafer pretreated in step 5) on a coating machine and 2 O 5-X The precursor solution was dropped onto the second surface of the silicon wafer and spin-coated at 6000 rpm for 30 seconds. Finally, the spin-coated silicon wafer was placed on a heating table preheated to 100°C for 10 minutes to obtain a uniform and dense V 2 O 5-X Film. V 2 O 5-X The film was heated at 150℃ in a mixed gas containing reducing gas (N 2 :H 2 =95:5) for 5 minutes to obtain a V of the first transition metal oxide with a thickness of 8 nm. 2 O 4.5 Thin films. V of the first transition metal oxides 2 O 4.5 The film is greater than 4.7 eV.

[0057] 7) Place the silicon wafer from step 6) in a thermal evaporation deposition device and start the vacuum pump to pump the pressure of the reaction chamber to 10 -3 Pa vacuum state, and then increase the current to 3 The evaporation boat of the powder is heated. 3 After the powder is completely melted, continue heating for a while to avoid contamination by impurities. The rate of deposition onto the first transition metal oxide V 2 O 4.5 On the film, a 5nm thick second transition metal oxide MoO 2.92 Thin film. Second transition metal oxide MoO 2.92 The work function is greater than 5.5 eV.

[0058] 8) Maintaining the original vacuum condition of step 7), heating the evaporation boat containing the Ag particles to The Ag electrode with a thickness of 100 nm was deposited at a rate of 100 nm to complete the preparation of the solar cell. 2 O 4.5 / MoO 2.92 / Ag structure solar cells.

[0059] Get as Figure 1The solar cell shown in the figure also includes, from top to bottom, a silver electrode grid line 1, a silicon nitride passivation layer 2, an N-type emitter 3, a P-type single crystal silicon substrate 4, a hole transport layer 5 and a silver electrode 6. The hole transport layer 5 includes a first transition metal oxide 51 and a second transition metal oxide 52 which are stacked, the first transition metal oxide 51 being close to one side of the P-type single crystal silicon substrate 4, and the second transition metal oxide 52 of the hole transport layer 5 being located on the side of the first transition metal oxide 51 away from the P-type single crystal silicon substrate 4.

[0060] Comparative Example 1

[0061] The difference from Example 1 is that step 7) is not included. In step 8), the silicon wafer is placed in a thermal evaporation deposition device, and the vacuum pump is started to pump the pressure of the reaction chamber to 10 -3 Pa vacuum state, the evaporation boat containing Ag particles is heated to The Ag electrode with a thickness of 100 nm was deposited at a rate of 100 nm to complete the preparation of the solar cell. 2 O 4.5 / Ag structure solar cells.

[0062] The JV parameters of the battery are obtained through testing, such as Figure 2 As shown, the p-Si / V 2 O 4.5 The output parameters of the Ag / H structure solar cell are: SC =39.6mA / cm 2 ,V OC =596mV, FF=69%, PCE=16.5%. 2 O 4.5 / MoO 2.92 The output parameters of the Ag / H structure solar cell are: SC =39.8mA / cm 2 ,V OC =619mV, FF=75%, PCE=18.4%. It can be seen that V 2 O 4.5 / MoO 2.92 The introduction of the stacked hole transport layer significantly improves the V OC , FF and PCE.

[0063] Example 2

[0064] The preparation of the solar cell of this embodiment is different from that of embodiment 1 in step 6) and step 7), and steps 6) and 7) are specifically as follows:

[0065] 6) Add 0.05 g of molybdenum powder to 10 mL of anhydrous ethanol and stir thoroughly. Then, add 350 μL of hydrogen peroxide to the solution and continue stirring until the powder is dissolved and the solution turns dark blue to obtain MoO 3-X Precursor solution. 0.05gNbCl 5 The powder was added to 10 mL of anhydrous ethanol and placed on a magnetic stirrer and stirred until the powder was completely dissolved to obtain NbCl 5 140 μL NbCl 5 Add 1 mL of MoO 3-X In the precursor solution, NbCl 5 and MoO 3-X The molar ratio is 5%, and the mixture is stirred thoroughly to obtain Nb 5+ :MoO 3-X Precursor solution.

[0066] Place the silicon wafer pretreated in step 5) on a gel coater and take 60 μL of MoO 3-X :Nb precursor solution was dropped onto the second surface of the silicon wafer and spin-coated at 8000 rpm for 30 seconds. Finally, the spin-coated silicon wafer was placed on a heating table preheated to 100°C and heated for 10 minutes to obtain a uniform and dense 15 nm thick Nb 5+ :MoO 2.5 : Thin film, the Nb 5+ :MoO 2.5 The film is a first transition group metal oxide.

[0067] 7) Place the silicon wafer from step 6) in a thermal evaporation deposition device, start the vacuum pump and pump the pressure of the vacuum evaporation reaction chamber to 10 -3 Pa vacuum state, and then by increasing the current to the V 2 O 5 The evaporation boat of the powder is heated. 2 O 5 After the powder is completely melted, continue heating for a while to avoid contamination by impurities. The second transition metal oxide V was deposited at a rate of 5 nm thick. 2 O 4.9 film.

[0068] The rest is similar to Example 1 and will not be described here. 5+ :MoO 2.5 / V 2 O 4.9 / Ag structure solar cells.

[0069] Comparative Example 2

[0070] The difference from Example 2 is that step 7) is not included. In step 8), the silicon wafer is placed in a thermal evaporation deposition device, and the vacuum pump is started to pump the pressure of the reaction chamber to 10 -3 Pa vacuum state, the evaporation boat containing Ag particles is heated to The Ag electrode with a thickness of 100 nm was deposited at a rate of 100 nm to complete the preparation of the solar cell. 5+ :MoO 2.5 / Ag structure solar cells.

[0071] The solar cells of Example 2 and Comparative Example 2 were tested to obtain the JV parameters. Figure 3 The p-Si / Nb of Comparative Example 2 can be obtained. 5+ :MoO 2.5 The output parameter of the solar cell with Ag structure is J SC =39.3mA / cm 2 , V OC =591mV, FF=66%, PCE=15.3%. 5+ :MoO 2.5 / V 2 O 4.9 The output parameter of the solar cell with Ag structure is J SC =39.1mA / cm 2 , V OC =638mV, FF=75%, PCE=18.6%. It can be seen that Nb 5+ :MoO 2.5 / V 2 O 4.9 The introduction of stacked films significantly improves the V OC and FF, because V 2 O 4.9 The film is closer to the chemical dosage ratio, providing a higher work function, increasing the silicon surface band bending, and promoting the selective transport of holes.

[0072] Example 3

[0073] The preparation of the solar cell of this embodiment is different from that of embodiment 1 in step 6) and step 7), and steps 6) and 7) are specifically as follows:

[0074] Step 6) 0.05 g WCl 6 The powder was added into 10 mL of n-propanol and stirred thoroughly until the powder was completely dissolved and the solution became transparent to obtain WO 3-x Precursor solution.

[0075] Place the silicon wafer pretreated in step 5) on a gel-spinning machine and take 60 μL of WO 3-x The precursor solution was dropped onto the second surface of the silicon wafer and spin-coated at 8000 rpm for 30 seconds. Then, the spin-coated silicon wafer was placed on a heating table preheated to 100°C for 10 minutes. 3-x The film was annealed in a nitrogen inert atmosphere at 200 °C for 20 min to obtain a 10 nm thick WO of the first transition metal oxide. 2.5 film.

[0076] 7) Place the silicon wafer from step 6) in a thermal evaporation device, start the vacuum pump and evacuate the vacuum evaporation reaction chamber to 10 - 3 Pa vacuum state, and then increase the current to 3 The evaporation boat of the powder is heated. 3 After the powder is completely melted, continue heating for a while to avoid contamination by impurities. The rate of deposition on the first transition metal oxide WO 2.5 The surface of the film was 15 nm thick and the second transition metal oxide MoO 2.92 film.

[0077] The rest is similar to Example 1 and will not be described here. 2.5 / MoO 2.92 / Ag structure solar cells.

[0078] The solar cells of Example 3 and Comparative Example 3 were tested to obtain JV parameters. Figure 4 The p-Si / WO of Comparative Example 3 can be obtained. 2.5 The output parameter of the solar cell with Ag structure is J SC =39.5mA / cm 2 , V OC =590mV, FF=64%, PCE=14.9%. p-Si / WO of Example 3 2.5 / MoO 2.92 The output parameter of the solar cell with Ag structure is J SC =39.7mA / cm 2 , V OC =633mV, FF=71%, PCE=17.8%. It can be seen that WO 2.5 / MoO 2.92 The introduction of the laminated film significantly improves the battery's V OC and FF, due to the nearly stoichiometric MoO 2.92The film provides a higher work function, increases the band bending of the silicon surface, and promotes the selective transport of holes.

[0079] The hole transport layer of step 7) of Example 2 and the hole transport layer of step 6) of Comparative Example 2 were tested for the minority carrier lifetime τ of the thin film. eff Values, such as Figure 5 As shown, in Comparative Example 2, Nb is introduced into the molybdenum oxide film. 5+ After that, its τ eff is 285.4μs. In Example 3, the vanadium oxide film is superimposed on the niobium-doped molybdenum oxide film, τ eff The effective lifetime of the hole transport layer in Example 2 of the present application is improved to 310.5 μs. The band structure of the niobium-doped molybdenum oxide in contact with p-Si in Example 2 and Comparative Example 2 is obtained by AFORS-HET simulation. Figure 6 It can be seen that in the niobium-doped molybdenum oxide / p-Si heterojunction of the first transition metal oxide, the energy band on the p-Si surface bends upward, while the energy band on the side of the niobium-doped molybdenum oxide close to the p-Si bends downward. The vanadium oxide of the second transition metal oxide further thermally evaporated in Example 2 has a higher work function, which can induce the energy band on the side of the niobium-doped molybdenum oxide close to the vanadium oxide to bend upward, thereby promoting the transport of holes.

[0080] Obviously, the above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, any modification, substitution, or improvement made on the basis of the above description and within the method and principle of the present invention should be included in the protection scope of the present invention. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the protection scope of the present invention.

Claims

1. A hole transport layer, characterized in that: The invention comprises a first transition group metal oxide and a second transition group metal oxide which are stacked and arranged in layers, wherein the second transition group metal oxide is closer to a stoichiometric ratio than the first transition group metal oxide.

2. The hole transport layer according to claim 1, characterized in that The first transition metal oxide comprises MoO 3-x , WO 3-y 、V2O 5-z One or more of the following, wherein x<2.8, y<2.8, z<4.7; the second transition metal oxide includes MoO 3-x , WO 3-y 、V2O 5-z One or more of the following, where x≥2.8, y≥2.8, z≥4.

7.

3. The hole transport layer according to claim 1 or 2, characterized in that: The first transition metal oxide is doped with low-valent metal cations, the chemical valence of the low-valent metal cations being lower than the chemical valence of the transition metal cations in the first transition metal oxide; optionally, the low-valent metal cations include V 5+ ,Nb 5+ ,Ta 5+ ,Sn 4+ , Al 3+ , Ni 2+ One or more of the .

4. The hole transport layer according to claim 3, characterized in that The work function of the first transition metal oxide is greater than or equal to 4.7 eV, and the work function of the second transition metal oxide is greater than or equal to 5.5 eV;.

5. The hole transport layer according to claim 1, 2 or 4, characterized in that: The thickness of the first transition group metal oxide and the second transition group metal oxide are both 1-15 nm.

6. A method for preparing a hole transport layer, characterized in that: include: forming a first transition group metal oxide on a substrate; A second transition group metal oxide is formed on a side of the first transition group metal oxide facing away from the substrate, wherein the second transition group metal oxide is closer to a stoichiometric ratio than the first transition group metal oxide.

7. The method for preparing a hole transport layer according to claim 6, characterized in that: The method of preparing a first transition metal oxide on a substrate comprises: Spin-coating a first precursor solution mixed with low-valent metal cations on a substrate, and heat-treating the solution to obtain a first transition metal oxide; optionally, the ratio of the amount of the low-valent metal cations to the amount of the first precursor in the first precursor solution is (1-10):100; Alternatively, a first precursor solution is spin-coated on a substrate, subjected to heat treatment, and then annealed in a reducing atmosphere, an inert atmosphere or vacuum conditions to obtain a first transition metal oxide; optionally, the annealing temperature is 100-200° C., and the annealing time is 5-20 minutes.

8. The method for preparing a hole transport layer according to claim 6, characterized in that: The second transition group metal oxide is formed on a side of the first transition group metal oxide facing away from the substrate, comprising: A second precursor oxide is vacuum evaporated on a side of the first transition metal oxide facing away from the substrate to obtain a second transition metal oxide.

9. A solar cell, characterized in that: The hole transport layer comprises the hole transport layer described in any one of claims 1 to 5, or the hole transport layer prepared by the preparation method of any one of claims 6 to 8.

10. The solar cell according to claim 9, characterized in that: The invention also includes, from top to bottom, a silver electrode gate line, a silicon nitride passivation layer, an N-type emitter, a P-type single crystal silicon substrate and a silver electrode. The hole transport layer is located between the P-type single crystal silicon substrate and the silver electrode. The first transition metal oxide of the hole transport layer is close to one side of the P-type single crystal silicon substrate, and the second transition metal oxide of the hole transport layer is located on the side of the first transition metal oxide away from the P-type single crystal silicon substrate.